PENGARUH FREKUENSI LATIHAN SATU MINGGU DAN DAYA LEDAK TUNGKAI TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK - Hamid, Abd. (Vidya Karya Jurnal Kependidikan, 2012)
This experimental research has objectives to find out the difference between the three-time-aweek training and the four-time-a-week training upon the result of tuck style long jump, and to find the difference of long term between high leg explosive and low leg explosive upon the result of tuck style long jump, and to figure out the interaction between the frequency of one-week training and leg explosive power upon the result of tuck style long jump. The result of the research in the first hypothesis testing indicated that there was a significantly different effect between the tree-time-a-week training frequency and the four-time-a-week training frequency on the result of tuck style long jump. The second hypothesis testing was that there was a significantly different effect between high leg explosive power and low leg explosive power upon the result of tuck style long jump. The third hypothesis testing was that there was a relationship between the a-week training frequently and the leg explosive to tuck style long jump.